Axial load–deformation behavior and fracture characteristics of bolted steel to laminated timber and glubam connections. (1st February 2023) - Shi, Da; Demartino, Cristoforo; Li, Zhi; Xiao, Yan
Abstract: Bolted steel to laminated composite bio-based material connections are commonly used in truss systems. The aim of this study is to provide a more rational understanding of their tensile axial behavior. The aim of this paper is twofold: first, it investigates and compares the monotonic tensile axial behavior of bolted steel to laminated timber and bamboo connections with slotted-in steel plates. The test matrix comprised a total of 8 different connection configurations obtained by changing parameters relevant to the connection behavior (Laminated Veneer Lumber (LVL) and Glued Laminated Bamboo (glubam), 2 bolt diameters, and 1 or 2 bolts). Three test repetitions for each connection configuration were performed to investigate the repeatability and assess variability. Tests were performed by also employing Digital Image Correlation (DIC) apparatus to monitor the deformation process and measure relative displacements of bolts. Moreover, the physical and mechanical properties of the materials adopted are investigated. Second, based on the experimental findings, a new monotonic load vs displacement phenomenological prediction model characterized by four stages is proposed which is capable of defining more rationally the observed tensile monotonic behavior and differentiating between brittle and ductile failures. An extensive discussion of the calibration and physical meaning of the proposed model by using the experimental test results as benchmark is provided. Highlights: Bolted steel to laminated timber or glubam connections with slotted-in steel plates. Axial load–deformation behavior and fracture characteristics. DIC to monitor the deformation process and measure relative displacements of bolts. New monotonic load vs displacement prediction model characterized by four stages. Calibration and physical meaning of the proposed model by using the experimental tests as a benchmark.